2006
DOI: 10.1111/j.1469-7580.2006.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic human neural progenitor cells transplanted into the neonatal hemiparkinsonian rat striatum differentiate into neurons and improve motor behaviour

Abstract: Neural stem cell transplantation is a promising strategy for the treatment of neurodegenerative diseases. To evaluate the differentiation potential of human neural progenitor cells (hNPCs) as a prerequisite for clinical trials, we intracerebrally transplanted in vitro expanded fetal mesencephalic hNPCs into hemiparkinsonian rats. On postnatal day one (P1), 17 animals underwent a unilateral intraventricular 6-hydroxydopamine injection into the right lateral ventricle. At P3, animals ( n = 10) received about 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…Here, we transplanted hNPCs derived from the ventral mesencephalic area of an 8-week-old human embryo into a DAdepleted striatum of adult rats. These cells have previously been shown to differentiate into TH-ir neurons accompanied by a behavioral benefit when transplanted into the lesioned striatum of juvenile animals [Hovakimyan et al, 2006]. In contrast to juvenile recipients, in the present parallel study, hNPC differentiation into DAergic neurons was not found, supporting the view of the environment as an instructive cue for neuronal specification and differentiation.…”
Section: Introductionsupporting
confidence: 36%
See 2 more Smart Citations
“…Here, we transplanted hNPCs derived from the ventral mesencephalic area of an 8-week-old human embryo into a DAdepleted striatum of adult rats. These cells have previously been shown to differentiate into TH-ir neurons accompanied by a behavioral benefit when transplanted into the lesioned striatum of juvenile animals [Hovakimyan et al, 2006]. In contrast to juvenile recipients, in the present parallel study, hNPC differentiation into DAergic neurons was not found, supporting the view of the environment as an instructive cue for neuronal specification and differentiation.…”
Section: Introductionsupporting
confidence: 36%
“…At the same time point, the sham control group (10 rats) received an injection of vehicle alone (1 l DMEM) using the same coordinates as for the transplantation group. Cells from the same passage and cell preparation were transplanted both in juvenile [Hovakimyan et al, 2006] and adult animals. To obtain similar conditions with our previous parallel transplantation study using these cells [Hovakimyan et al, 2006], no immunosuppression was performed.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [24][25][26] focus on the transplantation of immortalized progenitor cells in 6-OHDA Hemiparkinson animal models [24,25] and the differences in the abundance of this area of the brain at different points of development [26]. Hovakimyan et al [24] and Haas et al [25] as well as Schwarz and Freed [27] showed that the micro-environment of neonatal brains seems to be important for the differentiation of transplanted neuronal progenitors. Therefore, a further characterization of the abundance patterns of proteins during development in the Cx of the rat brain might provide a better understanding of neuronal development.…”
Section: Introductionmentioning
confidence: 99%
“…NSCs that can be harvested from the embryo around embryonic day (E) 14 -E15 in rodents [42,43,44] or 13 weeks post-fertilization in humans [45,46], are multipotent cells that have the ability to regenerate and also to give rise to neurons, oligodendrocytes and astrocytes that represent the three major cell lineages of the CNS [47]. Undifferentiated human fetal NSCs transplanted into the SNc of a MPTP ((1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine)-induced primate model of PD were able to survive, integrate and subsequently reduce some behavioral deficits [46].…”
Section: Fetal Neural Stem Cellsmentioning
confidence: 99%